INVESTIGAÇÃO TEÓRICA DOS MATERIAIS ZnO:Ba E (Ba, Zn)TiO3 - Lacerda, Luis Henrique da Silveira (2015)
Semiconductors materials are largely employed on development of innumerous optical and electronic due to their electronic, optical, ferroelectric and structural properties. Among the semiconductors materials stand out the zinc oxide (ZnO) and the barium titanate (BaTiO3) once shows excellent properties allied to low cost to obtaining. The ZnO is a simple oxide used in technology and largely investigated as an alternative to replace high cost material on development of electronic devices. Similarly, the BaTiO3 has perovskite crystalline structure whose properties present great technological interest. This work evaluated the effect of Ba presence on wurtzite structure and the influence of Zn atoms on tetragonal BaTiO3 properties. The obtained results indicates that the Ba atoms changes drastically the band structure of ZnO, resulting in the decrease of band gap for low quantities and the semiconductor type modification for doping above 25 %. The insertion of such atoms in wurtzite also causes the improvement of ferroelectric properties and the increase of unit cell lattice parameters. In case of Zn-doped BaTiO3, the doping process reduces radically de band gap and the ferroelectric properties regarding to pure material. Likewise, the semiconductor type is also modified by the Zn atoms presence. Based on obtained results for both crystalline systems, was proposed their employed in formation of p-n heterojunction. The heterostructure was evaluated through of four models. The obtained results for each one of these models were used to describe the interface region of ZnO/BaTiO3 heterojunction, proving that the atoms intercalation occurs and is responsible for heterostructure properties. Such properties present this heterostructure as a potential alternative for development of electronic devices, mainly the development of memory devices. The obtained heterostructure requires a low amount energy to electronic conduction process and shows high compatibility between the structure of heterojunction and the SiO2 substrate which is used in development of such devices.